Recovery of cobalt from lithium-ion batteries using fluidised cathode molten salt electrolysis. (20th September 2021) - Mirza, Mateen; Abdulaziz, Rema; Maskell, William C.; Tan, Chun; Shearing, Paul R.; Brett, Dan J.L.
Abstract: The future need to recycle enormous quantities of Li-ion batteries is a consequence of the rapid rise in electric vehicles required to decarbonise the transport sector. Cobalt is a critical element in many Li-ion battery cathode chemistries. Herein, an electrochemical reduction and recovery process of Co from LiCoO2 is demonstrated that uses a molten salt fluidised cathode technique. For the Li-Co-O-Cl system, specific to the experimental process, a predominance diagram was developed to aid in understanding the reduction pathway. The voltammograms indicate two 2-electron transfer reactions and the reduction of CoO to Co at −2.4 V vs. Ag/Ag + . Chronoamperometry revealed a Faradaic current efficiency estimated between 70-80% for the commercially-obtained LiCoO2 and upwards of 80% for the spent Li-ion battery. The molten salt electrochemical process route for the recycling of spent Li-ion batteries could prove to be a simple, green and high-throughput route for the efficient recovery of critical materials.